A critical discourse analysis of family literacy practices : power in and out of print - Rogers, Rebecca (Rebecca L.), 1959- (L. Erlbaum, 2003)
An exploration of the complexity of family literacy practices. It uses an in-depth case study of one African-American family, and discusses the attendant issues of power and identity, covering contemporary social debates about the connections between literacy and society.